1998
DOI: 10.1177/088840649802100103
|View full text |Cite
|
Sign up to set email alerts
|

The Shortage of Fully Certified Teachers in Special and General Education

Abstract: Tbere has long been concern in special education about the shortage of teachers who are fully certified in their main teaching assignment. Based on a national probability sample of 46,599 public school teachers, this research provides data on the certification status of both special and general education teacbers. Findings are presented for four types of teachers who enter the teaching force each year, and for two types of teachers who continue in public schools from the prior year. Results showed a chronic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 4 publications
0
46
0
Order By: Relevance
“…The most detailed national-level study of this type was reported by Boe, Cook, Bobbitt, and Terhanian (1998), who found that entering SETs (i.e., those not already employed as teachers) exacerbated the shortage of fully certified SETs. This is because 31.8% of entering SETs were partly certified, in contrast to only 7.8% of continuing SETs.…”
mentioning
confidence: 99%
“…The most detailed national-level study of this type was reported by Boe, Cook, Bobbitt, and Terhanian (1998), who found that entering SETs (i.e., those not already employed as teachers) exacerbated the shortage of fully certified SETs. This is because 31.8% of entering SETs were partly certified, in contrast to only 7.8% of continuing SETs.…”
mentioning
confidence: 99%
“…Billingsley and Cross (1992) report that the special education field loses many teachers to general education in their study based on the data collected from general and special education teachers in the United States. Similarly, Boe et al (1998) claim that a higher percentage of special educators transfer to general education than the reverse in their analysis based on a population of general and special education teachers in the United States. Additionally, in a study of Alaska teachers, Schnorr (1995) suggests that general education teachers who hold both general and special education certification mostly are not interested in transferring to special education.…”
Section: Discussionmentioning
confidence: 99%
“…Historically the right of passage to becoming a teacher has been teacher certification/licensure (Boe et al 1998;U.S. Department of Education 1998;Renzaglia et al 1997).…”
Section: Introductionmentioning
confidence: 99%